Efficacy and Safety of Shenfu Injection for Severe Pneumonia in the Elderly: A Systematic Review and Meta-Analysis Based on Western and Eastern Medicine - Shi, Shihua; Wang, Fei; Chen, Bonan; Pan, Jie; Luo, Dan; Pei, Caixia; Huang, Demei; Wang, Xiaomin; Wang, Yilan; Shen, Zherui; Li, Weihao; Wu, Yongcan; et al. (Frontiers in Pharmacology, 2022)
Background: Although increasing clinical trials studying Shenfu injection (SFI) composed of panaxoside 0.8mg/ml extracted from Panax ginseng C.A.Mey., and aconitine 0.1mg/ml extracted from Aconitum carmichaeli Debeaux, for elderly patients with severe pneumonia on biomarkers associated with COVID-19 progression are emerging, there is no evidence-based evaluation for the effect of SFI on elderly severe pneumonia. Objectives: To evaluate the effect of SFI on elderly severe pneumonia providing hints for treating critical COVID-19, we conducted a systematic review and meta-analysis. Methods: Nine databases, including PubMed, EMBASE, Web of Science, Science Direct, Google Scholar, Wanfang, Chongqing VIP Database, CNKI, and SinoMed were used to search clinical trials reporting the effect of SFI as an adjuvant for elderly severe pneumonia on outcomes of interest. Primary outcomes were the total effective rate, Acute Physiology and Chronic Health Evaluation (APACHE) II score, mortality, and safety. Second outcomes were predictors associated with COVID-19 progression. Duplicated or irrelevant articles with unavailable data were excluded. Cochrane Collaboration's tool was used to evaluate the risk of bias by two reviewers independently. All data were analyzed by Rev Man 5.4. Continuous variables were shown as weighted mean difference (WMD) or standard mean difference (SMD) with 95% confidence intervals (95% CI), whereas dichotomous data were calculated as the risk ratio (RR) with 95% CI. Results: We included 20 studies with 1, 909 participants and the pooled data showed that compared with standard control, SFI could improve the total effective rate (RR = 1.25, 95% CI = 1.14-1.37, n = 689), APACHE II score (WMD= −2.95, 95% CI = −3.35, -2.56, n=809), and predictors associated with COVID-19 progression (BNP, CK, stroke volume, cardiac output, LVEF, Cardiac output index, sE-selectin, vWF, APTT, platelet counts, D-Dimer, PCT, WBC). SFI may reduce mortality (RR = 0.52, 95% CI = 0.37 to 0.73, n = 429) and safety concerns (RR = 0.29, 95% CI = 0.17–0.51, n = 150) for elderly severe pneumonia. Conclusion: SFI as an adjuvant may improve the total effective rate, APACHE II score, gas exchange, and predictors associated with COVID-19 progression, reducing mortality and safety concerns for elderly patients with severe pneumonia.